Bomb Radiocarbon and the Hawaiian Archipelago: Coral, Otoliths, and SeawaterAbstract - Andrews, Allen H; Siciliano, Daria; Potts, Donald C; DeMartini, Edward E; Covarrubias, Stephannie (Radiocarbon, 2016)
Corals of the Hawaiian Archipelago are well situated in the North Pacific Gyre (NPG) to record how bomb-produced radiocarbon has been sequestered and transported by the sea. While this signal can be traced accurately through time in reef-building corals and used to infer oceanographic processes and determine the ages of marine organisms, a comprehensive and validated record has been lacking for the Hawaiian Archipelago. In this study, a coral core from Kure Atoll in the northwestern Hawaiian Islands was used to create a high-resolution bomb 14C record for the years 1939–2002, and was then used with other 14C measurements in fish otoliths and seawater to explore differences and similarities in the bomb 14C signal throughout the Hawaiian Archipelago. The Kure Atoll sample series produced a well-defined bomb 14C curve that, with some exceptions, was similar to other coral 14C records from the Hawaiian Archipelago. Subtle differences in the coral 14C records across the region may be explained by the large-scale ocean circulation patterns and decadal cycles of the NPG. The most rapid increase of 14C, in the 1950s and 1960s, showed similar timing across the Hawaiian Archipelago and provides a robust basis for use of bomb 14C dating to obtain high-precision age determinations of marine organisms. Reference otoliths of juvenile fish demonstrated the use of the post-peak 14C decline period as a viable reference in the age validation of younger and more recently collected fishes, and effectively extended the utility of bomb 14C dating to the latest 30 yr.